Romantic subjectivity and the endeavor to become a female travel writer in Sangkala di Langit Andalusia by Hanum Salsabiela - Risma Nur Rahmawati (Universitas Dian Nuswantoro, 2026)
This study examines how Hanum Salsabiela reveals herself while in Spain, based on her work entitled